1993
DOI: 10.1152/jappl.1993.74.3.1149
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine attenuates the exercise-induced increase in plasma [K+] in humans

Abstract: This study examined the dose-response effects of caffeine on plasma K+ balance during prolonged exercise. Two series of experiments were performed. In series A, 1 h after ingestion of 9 mg/kg dextrose (placebo) or 9 mg/kg caffeine, eight subjects cycled at 78% of peak O2 consumption until exhaustion; in series B, in four trials, 1 h after ingestion of 0, 3, 6, or 9 mg/kg caffeine, eight subjects ran on a treadmill at 85% of peak O2 consumption until exhaustion. Blood was sampled from an antecubital vein for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 0 publications
4
77
1
3
Order By: Relevance
“…Adenosine receptors are found in most tissues, including lipocytes and skeletal muscles (11), and activation of A 1 receptors leads to inhibition of lipolysis, activation of potassium channels, reduction in the atrioventricular node conduction, and inhibition of the basal and provoked neuronal activity (29). As caffeine acts as an adenosine-receptor antagonist, caffeine ingestion can thereby lead to elevation of free fatty acids before and during exercise (5,15), decrease the extracellular potassium concentration and by this promote action potential in muscle cells (4,26,29), and provoke release of the neurotransmitter serotonin that has a possible effect in mediating the feeling of fatigue (28,32). Caffeine is also associated with elevated plasma epinephrine, and glycogen sparing does occur in the active muscle, at least in the first few minutes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine receptors are found in most tissues, including lipocytes and skeletal muscles (11), and activation of A 1 receptors leads to inhibition of lipolysis, activation of potassium channels, reduction in the atrioventricular node conduction, and inhibition of the basal and provoked neuronal activity (29). As caffeine acts as an adenosine-receptor antagonist, caffeine ingestion can thereby lead to elevation of free fatty acids before and during exercise (5,15), decrease the extracellular potassium concentration and by this promote action potential in muscle cells (4,26,29), and provoke release of the neurotransmitter serotonin that has a possible effect in mediating the feeling of fatigue (28,32). Caffeine is also associated with elevated plasma epinephrine, and glycogen sparing does occur in the active muscle, at least in the first few minutes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-three peer-reviewed research articles met the inclusion criteria (Alves et al, 1995;Bell, Jacobs, & Zamecnik, 1998;Berglund & Hemmingsson, 1982;Bridge & Jones, 2006;Butts & Crowell, 1985;Cadarette, Levine, Berube, Posner, & Evans, 1983;Cha et al, 2001;Cohen et al, 1996;Collomp et al, 2002;Conway, Orr, & Stannard, 2003;Costill et al, 1978;Denadai & Denadai, 1998;French et al, 1991;Fulco et al, 1994;Graham, Hibbert, & Sathasivam, 1998;Graham & Spriet, 1991;Greer, Hudson, Ross, & Graham, 2001;Ivy et al, 1979;Jenkins, Trilk, Singhal, O'Conner, & Cureton, 2008;Lindinger, Graham, & Spriet, 1993;MacIntosh & Wright, 1995;McLellan, Bell, & Kamimori, 2004;McNaughton et al, 2008;Norager, Jensen, Madsen, & Laurberg, 2005;Pasman et al, 1995;Powers, Byrd, Tulley, & Callendar, 1983;Sasaki et al, 1987;Slivka et al, 2008;Spriet et al, 1992;Trice & Haymes, 1995;Van Soeren & Graham, 1998; Table 3). Three research articles Berglund & Hemmingsson, 1982;Butts & Crowell, 1985) reported Note.…”
Section: Study Characteristics For Caf Versus Placebo Analysismentioning
confidence: 99%
“…Caffeine can also prolong the endurance time and at the same time reduce the perception of fatigue during resistive breathing [24]. This last event is confirmed by lower levels of plasma K+ concentration with a subsequent potential increase of force generation in skeletal muscles and a possible delay of fatigue both at respiratory level and at that of skeletal muscles [25][26]. The net result could be an artificial improvement of physical performances.…”
Section: Stimulantsmentioning
confidence: 88%